1999
DOI: 10.1063/1.870190
|View full text |Cite|
|
Sign up to set email alerts
|

Laminar flow past a rotating circular cylinder

Abstract: The present study numerically investigates two-dimensional laminar flow past a circular cylinder rotating with a constant angular velocity, for the purpose of controlling vortex shedding and understanding the underlying flow mechanism. Numerical simulations are performed for flows with Re=60, 100, and 160 in the range of 0⩽α⩽2.5, where α is the circumferential speed at the cylinder surface normalized by the free-stream velocity. Results show that the rotation of a cylinder can suppress vortex shedding effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
170
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(220 citation statements)
references
References 21 publications
46
170
0
Order By: Relevance
“…It is important to mention that the two first values of the critical rotation are in agreement with the results obtained by Kang et al (1999) that have performed simulations for Reynolds numbers equal to 60, 100 and 160. Figure 11 shows the streamlines for flow past a rotating circular cylinder obtained in the present study for four different instants of time.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…It is important to mention that the two first values of the critical rotation are in agreement with the results obtained by Kang et al (1999) that have performed simulations for Reynolds numbers equal to 60, 100 and 160. Figure 11 shows the streamlines for flow past a rotating circular cylinder obtained in the present study for four different instants of time.…”
supporting
confidence: 76%
“…They obtained the velocity profiles, the skin friction coefficient, the stagnation and the separation points for different values of the specific rotation, which varied from 0 to 1.25. Kang et al (1999) presented a numerical study of two-dimensional laminar flow over a rotating circular cylinder by taking into account a constant angular velocity, with the aim of controlling the vortex shedding and better understanding the flow dynamic. The numerical simulations were performed for flows by taking into account three different values of Reynolds numbers: 60, 100 and 160 in the range of…”
Section: Introductionmentioning
confidence: 99%
“…They found the second unsteady flow mode in a very narrow range of (α L2 ≤ α ≤ α L3 ). Also, Kang et al (1999) found that drag and lift coefficients decrease with an increase in rotation rate. Badr and Dennis (1989) found a decrease in laminar forced convection heat transfer with increasing rotation rate for an isothermal cylinder for Re = 5,10,20,40 and 100 at α ≤ 4.…”
Section: Introductionmentioning
confidence: 99%
“…This computer program applies a control-volume method to integrate the equations of motion, constructing a set of discrete algebraic equations with conservative properties. In particular, the O-type grid modified structure similar to that adopted by Kang et al (1999) was created here. The unsteady, laminar, segregated solver was employed here to solve the incompressible flow on the collocated grid arrangement.…”
Section: Numerical Detailsmentioning
confidence: 99%
See 1 more Smart Citation